2014
DOI: 10.1093/her/cyt118
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' perceptions of female genital mutilation

Abstract: The practice of female genital mutilation (FGM) is widespread in Nigeria. This study was conducted to assess the perceptions of FGM among mothers at a primary healthcare centre in Lagos, Nigeria. A convenience sample of 95 mothers completed the pre-tested, semi-structured questionnaires. Data analysis was carried out using descriptive statistics and a chi-square test was used to test for association between variables. Findings showed that the mothers held ambivalent beliefs about the practice. Although over ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 11 publications
1
39
1
Order By: Relevance
“…A study done in Nigeria showed the existence of ambivalent beliefs among mothers about the practice. Although over half of the respondents (56.8%) perceived FGC as not being beneficial, 44.2% of the participants support FGC [12]. Another study in Nigeria also stated that educated mothers were found to be less likely to favor the cutting of their daughters [13].…”
Section: Introductionmentioning
confidence: 99%
“…A study done in Nigeria showed the existence of ambivalent beliefs among mothers about the practice. Although over half of the respondents (56.8%) perceived FGC as not being beneficial, 44.2% of the participants support FGC [12]. Another study in Nigeria also stated that educated mothers were found to be less likely to favor the cutting of their daughters [13].…”
Section: Introductionmentioning
confidence: 99%
“…The other factor in the current study is the increased mean age (36.93 ± 8.42) of the respondents, which might be enough time to forget this bad experience, especially when no long-term complications were faced. Nonetheless, negative attitude towards FGM was significantly associated with previous circumcision, as reported by medical students, who participated in a previous Egyptian study [27].…”
Section: Discussionmentioning
confidence: 80%
“…Despite that, there is still a need for ongoing campaigns, offering direct contact with the mothers to correct misconceptions, answer questions and alleviate worries. In the same line, Ahanonu and Victor [27] found that, over half of the respondents viewed FGM as harmful; nonetheless, they thought that it prevents sexual promiscuity and contributes to faithfulness to the husband. Moreover, Abo and Gbadebo [28], that, Egyptian medical students had a modest knowledge about FGM and a neutral attitude towards it as well.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations